Higher-order Aberrations — the Choice of Optimal Intraocular Correction in the Surgical Treatment of Cataracts. Review of the Literature - D. A. Khvan; G. A. Fedyashev (Oftalʹmologiâ)
The cornea is the most powerful refractive element of the eye and plays a fundamental role in the quality of vision. Imperfection of corneas shape leads to the focusing errors formation, known as optical aberrations, which are responsible for visual performance deterioration. Understanding and assessing wavefront errors in IOL selection and calculation is great importance to achieve maximum optical outcome in the postoperative period. The article presents literature data of the effect of higher-order aberrations on the vision quality in unoperated eyes, changes of the wavefront in the eyes after cornea surgical interventions, the effect of various types of IOLs (spherical, aspherical, multifocal and EDOF) on the total error of the eye wavefront, recommendations at their choice with different severity levels of optical aberrations, as well as promising areas of research on this issue.